Multiple drug resistance and plasmid profilling in Salmonella Galiema, Salmonella Typhimurium, Salmonella Virchow and Salmonella Heidelberg - TAMULY, SHANTANU; SAXENA, M K; ., SONAL; AMBWANI, T; LAKHCHAURA, B D (The Indian Journal of Animal Sciences, 2011)
In the study reported here, 30 isolates of Salmonella enterica (6 Galiema, 9 Virchow, 6 Typhimurium and 9 Heidelberg) obtained from poultry fecal and egg samples were analyzed for plasmid pattern and susceptibility to a panel of antimicrobial agents namely carbenicillin, aztreonam, ampicillin, fosfomycin, cefprozic, piperacillin, meropenem, ticarcillin, levofloxacin, cefepime, cefpodoxime, cefdinir, cefixime, chloremphanicol and gentamicin. Intermediated sensitivity was found in 1 isolate of Salmonella Galiema against levofloxacin and in 2 isolates of Salmonella Typhimurium against fosfomycin. While the rest 28 isolates were resistant against all the 15 antibiotics.. On plasmid profiling, 85 kb plasmid was common in all the isolates.. While this plasmid was absent in the 4 control Salmonella isolates of Salmonella Gallinarum with known sensitivity against all the tested antibiotics. From our preliminary study we have concluded that this plasmid in the Salmonella carries the genes that resulted in multiple drug resistance. Â